2011
DOI: 10.1007/s11695-011-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Omental Gene Expression of Adiponectin Correlates with Degree of Insulin Sensitivity Before and After Gastric Bypass Surgery

Abstract: Background and Aim Circulating adiponectin is known to correlate negatively with insulin resistance in patients with obesity and diabetes. The aim of this study was to assess the effect of gastric bypass (GB) surgery on adiponectin gene expression in subcutaneous and omental adipose tissues. Methods Adipose tissues and plasma were obtained from 25 subjects undergoing GB surgery, 15 non-obese subjects, and 12 subjects after GB surgery. Real-time quantitative reverse transcription polymerase chain reaction (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…In another study of 25 women undergoing elective gynecological surgeries, adiponectin expression was higher in SAT compared to omental AT in both lean and overweight women [ 22 ]. Furthermore, Chen and colleagues found that omental expression of adiponectin was much higher after weight loss with gastric bypass surgery when compared to age-matched obese controls undergoing the same surgery and matched non-obese controls [ 23 ]. Our study evaluated AT (in contrast to adipocytes) secretion of adiponectin in a relatively large sample size of both men and women (in contrast to studies limited to women).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 25 women undergoing elective gynecological surgeries, adiponectin expression was higher in SAT compared to omental AT in both lean and overweight women [ 22 ]. Furthermore, Chen and colleagues found that omental expression of adiponectin was much higher after weight loss with gastric bypass surgery when compared to age-matched obese controls undergoing the same surgery and matched non-obese controls [ 23 ]. Our study evaluated AT (in contrast to adipocytes) secretion of adiponectin in a relatively large sample size of both men and women (in contrast to studies limited to women).…”
Section: Discussionmentioning
confidence: 99%
“…These findings point strongly towards adipose tissue regaining its endocrine capacity after surgery. It has also been reported that SAT expression of leptin goes down after RYGB whereas adiponectin gene expression in primarily SAT was reported to increase in only one out of five studies . In the context of these findings it is worth mentioning the novel hypothesis that adiponectin is produced in significant amounts by adipocytes in the bone marrow .…”
Section: Adipokine Secretionmentioning
confidence: 92%
“…Similar results were recently reported by Chen et al, who analysed adiponectin gene expression in the omental adipose tissue in 40 patients, of whom 25 were obese and showed an inverse correlation with HOMA-IR. In the same study, adiponectin gene expression was significantly increased (by about five times) after gastric bypass intervention, paralleling the improvement in insulin resistance [26].…”
Section: Discussionmentioning
confidence: 70%